Hubble Space Telescope exhibition display - Perkin-Elmer Corporation (1985)
Group photograph of members of the Perkin-Elmer Corporation's Optical Group posed in front of an exhibit display related to the Hubble Space Telescope. The individuals present in the photograph are unidentified. A manufacturer of analytical instruments, diagnostic tools, and medical imaging equipment, Perkin-Elmer was commissioned to build the optical components of the Hubble Space Telescope.
Keywords: Employees; Perkin-Elmer Corporation; Scientific apparatus and instruments; Hubble Space Telescope (Spacecraft); Corporations